Evaluation of needle trap micro‐extraction and solid‐phase micro‐extraction: Obtaining comprehensive information on volatile emissions from in vitro cultures. (5th June 2018) - Oertel, Peter; Bergmann, Andreas; Fischer, Sina; Trefz, Phillip; Küntzel, Anne; Reinhold, Petra; Köhler, Heike; Schubert, Jochen K.; Miekisch, Wolfram
Abstract: Volatile organic compounds (VOCs) emitted from in vitro cultures may reveal information on species and metabolism. Owing to low nmol L −1 concentration ranges, pre‐concentration techniques are required for gas chromatography–mass spectrometry (GC–MS) based analyses. This study was intended to compare the efficiency of established micro‐extraction techniques – solid‐phase micro‐extraction (SPME) and needle‐trap micro‐extraction (NTME) – for the analysis of complex VOC patterns. For SPME, a 75 μm Carboxen®/polydimethylsiloxane fiber was used. The NTME needle was packed with divinylbenzene, Carbopack X and Carboxen 1000. The headspace was sampled bi‐directionally. Seventy‐two VOCs were calibrated by reference standard mixtures in the range of 0.041–62.24 nmol L −1 by means of GC–MS. Both pre‐concentration methods were applied to profile VOCs from cultures of Mycobacterium avium ssp. paratuberculosis . Limits of detection ranged from 0.004 to 3.93 nmol L −1 (median = 0.030 nmol L −1 ) for NTME and from 0.001 to 5.684 nmol L −1 (median = 0.043 nmol L −1 ) for SPME. NTME showed advantages in assessing polar compounds such as alcohols. SPME showed advantages in reproducibility but disadvantages in sensitivity for N‐containing compounds. Micro‐extraction techniques such as SPME and NTME are well suited for trace VOC profiling over cultures if the limitations of each technique is taken into account.